The Virtual Production Line as a model for the innovative global economy - Stanislaw Walukiewicz (European Regional Science Association (ERSA), 2016)
By an example of the Linux system, I introduce a concept of the Virtual Production Line (VPL) as an extension of an assembly line, brought in by Henry Ford in motor industry a hundred years ago, and demonstrate its usefulness in an analysis of open source software development. The line is virtual, since it does not exist physically and developers may be located in different parts of the world, exchanging information via Internet, but they join their efforts in fixing certain bug(s) or extending some parts of a codebase. So, there exists a one to one correspondence between a Linux project and its VPL. Then, motivation and governance in a Linux project can be studied as formal and informal relations (social capital) among developers working on a given VPL. This paper proposes the VPL as a new model for an analysis and evaluation of creative labor done by Linux developers on the corresponding VPL, and generalizes these findings to the case of any creative activity. It is useful to divide a work (labor) into routine and creative and define a creative work as a here and now negation of a routine one. For instance, using computers and the Internet was creative in the scientific community (here) some 25 years ago (then), but it is a routine activity in 2016 (now). Scientists who do not use computers and the Internet are exceptions that prove the previous sentence here (scientific community) and now (2016). A work of a blue collar on an assembly line is a commonly used example of a routine labor. In the innovative global economy, I claim, people will do mostly creative labor working under projects on corresponding Virtual Production Lines. A success of a given project depends on formal and informal relations (social capital) among the experts working on the VPL. Social capital, in turn, can be modeled and measured as cognitive and emotive proximities among these experts. The paper provides new measures for cognitive and emotive proximity and suggests generalizations of its theoretical findings. As a practical implication, the paper describes the sequential assignment method which can be used in organization and management of project teams. As an application, I study the open innovation movement from the VPL perspective, and consider two research questions: (1) why do individuals participate in the open innovation projects, and (2) how their work is organized and managed, in particular. The main conclusion says that the Linux system can be considered as an example of a completely new way of organization and evaluation of creative labor in the innovative global economy. I call it the Linux world.
Keywords: 330; Innovative global economy; open source software; Linux system; human and social capital; cognitive and emotive proximities; project management; open innovation